Perubahan Sosial Budaya Masyarakat Kasepuhan Adat Banten Kidul-Kabupaten Sukabumi - Z. Mutaqin; Wahyu Iryana (UIN Sunan Gunung Djati Bandung, 2018)
The Kasepuhan Adat Banten Kidul in Sirnaresmi Village is a traditional society that still holds the legacy of their ancestors. Along with the development of incoming science and technology, gradually this traditional Kasepuhan society experienced a cultural change. Cultural changes that occur as a result of the challenge and response of Kasepuhan adat community to new things so that there has been acculturation of culture.The purpose of this study is to find out how the general description of Desa Sirnaresmi and to know the cultural changes Kasepuhan Adat Banten Kidul people in the Village Sirnaresmi District Cisolok Sukabumi.The method used in this research is historical method. Historical research model is a method that studies events and events in the past based on abandoned sources. This research method is done through four stages, namely heuristic, critic, interpretation, and historiografi.The results of the research in the field can be concluded that there has been a cultural change in Kasepuhan Adat Banten Kidul in Sirnaresmi Village, Cisolok Subdistrict of Sukabumi Regency, this is indicated by changing aspects of language, technology, livelihood, religious system, community system, knowledge and art system. Changes in the culture of Kasepuhan Adat Banten Kidul in Sirnaresmi Village occurred significantly in the early 2000s, when it was repaired by road facilities connecting with the Kecamatan center and after the entry of electricity in the area. The existence of more adequate facilities, making the Kasepuhan Adat Banten Kidul more intensely interacting with the outsiders and the indigenous people of Kasepuhan have been able to follow the development of the outside community. The Kasepuhan Adat Banten Kidul, which is a traditional society that still preserves its ancestral tradition, initially did not respond positively to the new things but gradually they began to follow. This is further supported when the entry of the telecommunications network, so that interaction with the outside community is increasingly massive and make the indigenous people of Kasepuhan has started to leave the tradition of her ancestral heritage because it replaced by incoming outer culture. Acculturation between indigenous cultures and outside cultures that enter, create the birth of a new culture. Subastansial things begin to be abandoned and replaced by a new culture that comes from outside and is considered more modern.